INTENSI PERILAKU DAN RELIGIUSITAS GENERASI MILLENIALS TERHADAP KEPUTUSAN PEMBAYARAN ZIS MELALUI PLATFORM DIGITAL - Mega Rachma Kurniaputri; Rindani Dwihapsari; Nurul Huda; Nova Rini (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2020)
Indonesia has the largest number of Muslim in the world, therefore the potential of zakat can reach 3.46 percent of GDP. But in fact, total collection of zakat is not accordance with its potential. One of the solution which can be done is approach the millennial generation and take advantage of current financial technology. Along with the issue, the purpose of this research is to examine the faktors that influence millennials generation in Jabodetabek in their decision to pay zakat, infaq and alms through digital platforms. Based on the literature review, behavioral intentions will affect individual behavior of consuming an item or service, which in this study is behavior in deciding to pay ZIS through a digital platform such as OVO, GoPay, mobile banking. In addition, religiosity is a form of individual behavior towards their religion and it can influence the decisions to pay ZIS. By using PLS-SEM analysis, as well as survey data from the distribution of questionnaires to 153 respondents, it was found that intention behavior was significantly influential in the decision to pay ZIS through digital platform. While religiosity has no significant effect on the decision to pay ZIS through a digital platform.